A representação da consoante em final de sílaba em textos de alunos da EJA - Assis, Maria das Mercês Cardoso de (2016)
Through this paper work, we aim to describe phonologic processes, involving syllables ending in consonant, reflected in the writing of 9th grade studants from the program of Youngs and Adults Education (EJA - in the portuguse acronym) - 2nd segment, in order to analyse the most frequent coda substitutions, inserts and erasement, that interfere in the domain of ortographic writing and, from that, propose and apply an intervention through a sequency of activities. The corpus consists in one hundred (100) texts from the EJA 9th grade students from a public school in Distrito Federal, situated in Sobradinho II, collected, after the apply of individual wrinting production. It was done some surveys and data analysis to verify which phonologic process (substitution, insert or erasement) occured in coda more frequently and in more number, to, then, apply an intervention in classroom, by a sequency of activities. The analysis results shows the erasement as the biggest occurrence, indicating a strong orality influence in the writing, which stands out the linguist variation used by our students. This way, it is important for us to reflect about the relations there are between, orality and liguistic variation and the interference of them in the writing. From the results, we prepared a didactic proposal that has as objective leads the EJA student to a better comprehension of the language occurrences and, this way, decrease or repair the present problem. Through this proposal, we also want to contribute for the teachers' reflection, regarding the importance of the study aspects of phonetic and phonology, seeking to improve the teaching - learning in the writing and, consequently, collaborating with a quality education, that makes the diference in our teaching practice and in the students' lives. As part of the theorical framework, was used as base the contributions of phonology studies, specifically, on the syllabe studies of Câmara Jr. (2015), Bisol(2005/2009), Abaurre (1999), Callou (1993), Silva (2009, 2011, 2014), Bortani-Ricardo (2005, 2011) and Cagliari (2008), among others, to bring a discussion around our research object.